1979
DOI: 10.1017/s0014479700009200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Soil Salinity on Broad Bean (Vicia faba) in the Sudan

Abstract: The effect of soil salinity on growth and yield of broad bean was investigated, using correlation analysis. The salinity level at which 50% reduction in bean yield occurred was 9 mmho/cm. The negative correlation between dry matter production and yield and ECe, together with the field observations, indicated that soil salinity may be responsible for the different growth and yield of broad bean fields in the salt-affected areas of northern Sudan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…El-Karouri (1979) studied the effect of soil salinity on growth and yield of a local Sudanese cultivar and Effect of temperature on ovule fertilization frequency (%) in inbred and hybred flowers after 24 h and 36 h incubation found it to have medium tolerance . This disagreed with the earlier findings of Ayers & Eberhard (1960) who classified faba beans as having low salt tolerance .…”
Section: Salinitymentioning
confidence: 99%
“…El-Karouri (1979) studied the effect of soil salinity on growth and yield of a local Sudanese cultivar and Effect of temperature on ovule fertilization frequency (%) in inbred and hybred flowers after 24 h and 36 h incubation found it to have medium tolerance . This disagreed with the earlier findings of Ayers & Eberhard (1960) who classified faba beans as having low salt tolerance .…”
Section: Salinitymentioning
confidence: 99%
“…Toxicity symptoms of salinity have been described for chickpea (Saxena, 1987 ;Chandra, 1980) and faba bean (El-Karouri, 1979) . A rating scale of 1 to 5 (van Rheenen & Sethi, 1990) or 1 to 9 (Saxena, 1987) has been used in field screening of chickpea on naturally occurring saline fields .…”
Section: Salinitymentioning
confidence: 99%
“…The threshold salinity level (EC at which reductions in growth and yield commence) is considered an important index for salt-sensitive crops such as chickpea . EC or EC e at which 50% reduction in shoot mass or seed yield occurs also has been used as a selection criterion in chickpea (Chandra, 1980 ;Saxena, 1987 ;Johansen et al, 1990) and faba bean (El-Karouri, 1979) .…”
Section: Salinitymentioning
confidence: 99%
See 1 more Smart Citation
“…It is considered to be one of the most important grain legume crops in Syria. Faba bean is a moderately salt-tolerant plant species, with a yield decrease of 50% at soil electrical conductivity (EC) values ranging between 9 and 11 dS m -1 (Lockerman et al, 1983;El-Karouri, 1970). Other studies demonstrated that the dry matter production and nodulation in faba bean decreased when irrigated with saline effluent containing an EC of 10 dS m -1 (Ban-Uelos et al, 2002).…”
Section: Introductionmentioning
confidence: 99%